Analysis of a Tall Structure Considering Mivan Technology Under Lateral Load Using ETABS - Jatin Kushwaha; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
High rise structures are prepared to resist seismic loads besides such massive stcutures are even subjected to wind load due to the magnitude and nature of wind load, hence such load factors are determined to understand its behaviour. This research is primarily focused to understand the behaviour of the wind response on high rise structures considering a G+15 structure. Mivan structure was analyzed in the study considering slab wall system instead of moment resisting fame for the structure. This study focuses on the level anomalies by considering various shapes in the arrangement of the building. Extents of wind loads are reliant upon the space of openness of the structure, thus the state of the structure must be considered with due significance as the space of openness is subject to shape. The diverse formed structures will have various reactions to the applied lateral load. Henceforth in this study, an endeavor has been made to foresee the impact of various states of structures for wind loads. The wind load is applied as per I.S. 875 part III:2015 specifications.